O helenismo à luz da leitura de Sexto Empírico: considerações céticas sobre o viver bem - Silva, Wellington Faustino de Melo da (2021)
The present study consists of an investigation regarding hellenism in the light of what the skeptic Sextus Empiricus wrote (2nd century AD). Based on the reading of Outlines of Pyrrhonism and Adversus Mathematicos, book XI, the sextian interpretation of the so-called dogmatic hellenistic philosophies is analyzed, especially in the context of discussions on the topic of ethics. Furthermore, but through this examination, a deepening of the skeptical philosophy itself will take place, whose efforts go towards better understanding the notions of suspension of judgment (epokhé), imperturbability (ataraxia), and appearance (phainoména) within the pyrrhonian corpus. In order to fulfill these purposes, it begins with the investigation of the arguments responsible for establishing the skeptical aporia in face of the contradictions perceived in the dogmatic path of philosophy. After that, Sextus' perception of hellenic eudaimonism is examined, a moment in which strong objections to ethical science will be revealed, understood as the one responsible for establishing lessons related to living well. The sextian interrogations will culminate both in the impossibility of considering it properly an art and in the neutralization of dogmatic ethical conceptions. It is, as will be clear, a hermeneutic of the sextian text in the sense of exploring ethical discussions.